LOCAL WISDOM IN THE USE OF PLANTS FOR HOUSEHOLD NEEDS BY THE DAYAK BENUAQ IN KAMPUNG LOTAQ, EAST KALIMANTAN - Sepsamli, Letus; Diana , Rita; Nugroho, Andi; Hastaniah, Hastaniah; Christian Dini, Gabriella; Matius, Paulus (Forestry Study Program University Of Mataram, 2025)
The Dayak Benuaq in Kampung Lotaq possess local wisdom in using the plants around them to meet household needs. The diversity of plant species used for household needs has been maintained until now. This research aims to examine the types of plants and local wisdom in using plants for household needs among the Benuaq Dayak tribe in Kampung Lotaq, Muara Lawa, East Kalimantan. This research applies purposive sampling in selecting informants. The number of informants in this study is 15 people. The results of this study show that there are 20 species of plants used for household needs, namely 10 types used as firewood (fuel) and 10 types used to make household utensils. The plant family that dominates for household needs is Arecaceae. Plants that are often used as fuel are kelepapak (Vitex pinnata L) and rubber (Hevea brasiliensis Muell.Arg.) because they dry quickly and produce a lot of embers, while the plants commonly used to make household utensils are uwe or rattan (Calamus sp.) and teluyent or ulin (Eusideroxylon zwageri) because they are strong and durable. The Dayak Benuaq community in Kampung Lotaq still preserves local wisdom by utilizing plants to meet household needs.